The impact of filtering self‐organizing maps: a case study with Australian pressure and rainfall. (12th April 2014) - Huva, Robert; Dargaville, Roger; Rayner, Peter
ABSTRACT: This study presents a semi‐objective set of criteria for filtering the time series of a self‐organizing map (SOM, a method for collapsing a complex data set onto a series of typical instances/nodes). The purpose of the filter (or selection process) is to avoid the problem of associating anomalous time steps with SOM nodes that do not adequately describe that time step. The filter is based on measures of the match of the original field to the nearest SOM node. We demonstrate the method by using 21 years of MSLP reanalysis data for the Australian region from the European Centre for Medium Range Weather Forecasting product, ERA‐Interim. We show that there are instances in which the SOM is incapable of describing the original data and that these instances can be removed using a set of criteria. We then show that this filtering/removal process improves both the quantitative and qualitative matching of the SOM to the MSLP data. Finally, we show that SOM‐associated precipitation at three Australian cities (Melbourne, Sydney and Perth) is significantly influenced by the MSLP distributions that do not relate to the SOM and were removed by the filtering. The results show that care is required when interpreting trends inferred from data sorted into SOM nodes.